Hubungan Dukungan Suami terhadap Kecemasan Pasien Pertama Kali di Indikasi Sectio Caesarea - Arista Mayasari; Rinda Intan Sari; Anis Ardiyanti (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Childbirth, whether through vaginal delivery or Cesarean section (CS), is a significant event often accompanied by psychological challenges such as anxiety, particularly among women undergoing CS. This quantitative study aimed to explore the correlation between spousal support and anxiety levels in 40 first-time CS candidates. Using purposive sampling, this research employed the Hamilton Anxiety Rating Scale (HARS) and the Spousal Support Questionnaire as measurement tools. The majority of respondents were aged 26-35 years (80%), in their third trimester of pregnancy (100%), primigravida (80%), and presented with indications for CS (65%). All respondents reported receiving supportive spousal support during their pregnancy. The study revealed that 70% of mothers experienced mild anxiety, with only 5% reporting moderate anxiety. Statistical analysis using the Spearman rank test demonstrated a significant relationship between spousal support and anxiety levels among first-time CS candidates (p = 0.034, p < 0.05). This suggests that higher levels of spousal support correlate with lower anxiety levels in expectant mothers undergoing CS. The findings underscore the importance of spousal support during pregnancy and childbirth, highlighting the need for partners to accompany and provide emotional support to mitigate anxiety. Future research should explore additional factors influencing anxiety and consider interventions to enhance support mechanisms for expectant mothers undergoing CS.